Santri Patriot Scholarship Program: Efforts to Meet the Needs of Management Cadres at Nurul Jadid Paiton Islamic Boarding School In Probolinggo - Wahid, Najiburrahman (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
Every citizen of school age from elementary to tertiary level must receive an education. But in reality, many school-age citizens still cannot get a significantly higher education. Sometimes, students have high achievements but are hampered by the study process. On the other hand, some students drop out in the middle of their study journey for lack of cost. Meanwhile, the number of students entering the Nurul Jadid Islamic Boarding School every year continues to increase. Where the ratio of administrators to students is increasingly non-standard, it affects the guardian services and student guidance in the dormitory during the study process because the period of education for secondary education students is longer than the period of teaching in higher education, which is taken by cadres of Islamic boarding school management. Realizing this, finding a way out for students with economic constraints is essential. For this reason, Nurul Jadid University, which is one of the universities in Islamic boarding schools, seeks solutions for students who are constrained economically but have a strong spirit to continue their education while serving by providing an independent scholarship called Santri Patriot Scholarship since 2016 to students at Nurul Jadid University spread across various majors with a different number of recipients from year to year. This is to avoid the opportunity for prospective students to withdraw from the study process and as a continuous effort for management cadres in student dormitories. The provision of this patriot student scholarship includes education costs, life skills training and national insight, entrepreneurship, and religious competence, which aims to spur achievements and competencies to be then implemented as provisions in carrying out the mandate as administrators, mu'allimah, and guardians in student dormitories, as well as conditions when they return to the community. So far, after seven years of running, the number of applicants for this scholarship path continues to grow. The scholarship recipient students take advantage of the opportunities provided and get plus value from the service experience and life skills learning they get during their education.